2005
DOI: 10.1111/j.1468-1331.2004.00954.x
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial arterial and arteriovenous malformations presenting with infarction. Lausanne Stroke Registry study*

Abstract: Cerebral aneurysms and arteriovenous malformations (AVMs) are well-known sources of intracranial hemorrhage, but can also manifest as other clinical symptoms or remain clinically asymptomatic. The aim was to document and analyze cases of aneurysm or AVM with brain infarction. Survey on 4804 stroke patients treated at the Department of Neurology, Centre Hospitalier Universitaire Vaudois, Lausanne, Switzerland between 1978 and 2000 using the Lausanne Stroke Registry. Twenty patients presented with cerebral aneur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 47 publications
1
12
0
4
Order By: Relevance
“…7,[13][14][15]21,22 Guo et al 13 reported a perinidal steal in brain AVMs and described 3 types of perfusion disturbance. In type 1, CBF and cerebral blood volume (CBV) ratios were increased in the immediate and remote perinidal regions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7,[13][14][15]21,22 Guo et al 13 reported a perinidal steal in brain AVMs and described 3 types of perfusion disturbance. In type 1, CBF and cerebral blood volume (CBV) ratios were increased in the immediate and remote perinidal regions.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of perifocal CBF abnormalities in previous studies may be due to shortcomings in previous imaging methods with lower spatial resolutions. 7,15 It has been suggested that reduced arterial and raised venous pressures in AVM feeders are sufficient to compromise resting-state CBF adjacent to the AVM. 23 The inhomogeneous effect of the macrovascular AVM flow on the perfusion within the territory of the feeding artery in our study confirms such a second level of local perfusion impairment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…UIAs are incidentally found when a brain MRA is performed in asymptomatic healthy volunteers 6,7 ; UIAs in stroke patients are also incidentally detected 2,5,6,[8][9][10] . Some previous studies indicated that cerebrovascular diseases seem to increase the occurrence of UIAs 5,11 .…”
mentioning
confidence: 99%
“…Cerebral arteriovenous malformation (CAVM), which is a common intracranial vascular deformity, is a well-known cause of intracerebral, intraventricular, and subarachnoid hemorrhage and other clinical symptoms [1]. CAVM occurs due to lack of direct fistula between the cerebral arteriovenous capillaries, which lead to the appearance of arteriovenous short-circuit and cause arteriovenous direct connectivity that intrigues a series of abnormal hemodynamics manifested in various clinical symptoms and signs [2].…”
Section: Introductionmentioning
confidence: 99%